Bulky aryl functionalized carbazolyl ligands: amido alternatives to the 2,6-diarylphenyl ligand class? - Coombs, N; Stasch, A; Cowley, A; Thompson, A; Aldridge, S (2008)
Sterically encumbered amido ligands based on a 1,8-diarylcarbazol-9-yl backbone have been investigated as electronically distinct alternatives to the widely-used terphenyl ligand class in the stabilization of low-coordinate metal complexes, and structurally characterized for the first time. While 1,8-diphenylcarbazol-9-yl derivatives are readily available, facile rotation about the Cipso-Cipso bonds leads to structurally characterized main group derivatives {e.g., [(1,8-Ph,-3,6-Me2C12H4N)K]2} in which the coordination geometry at the metal centre is augmented by secondary metal arene interactions. By contrast, the extra bulk inherent in the corresponding 1,8-dimesityl ligand results in essentially perpendicular alignments of the arene and carbazole planes, and a substituent-enforced sterically protected pocket. Comparative structural studies of complexes containing the GaCl2 fragment imply that the 1,8-dimesitylcarbazol-9-yl framework offers greater steric protection at the metal centre than does the corresponding 2,6-dimesitylphenyl ligand.